The Effectiveness of Coaching-Based Academic Supervision in Improving Teacher Performance: (Efektivitas Supervisi Akademik Berbasis Coaching dalam Meningkatkan Kinerja Guru) - Arina Santi; Nurdiansari; Nur Khayati; Ami Aulia; Warman (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2024)
ABSTRACT Academic supervision based on coaching is a professional development approach that emphasizes collaboration, reflection, and teacher empowerment in improving instructional performance. This article aims to analyze the effectiveness of coaching in academic supervision through a literature review of relevant theories and research. Using a narrative review method, studies from the last five years were examined to identify the fundamental concepts of coaching, its implementation within academic supervision, and its contributions to enhancing teacher competence. The findings indicate that coaching strengthens teachers' pedagogical, professional, and managerial competencies through dialogic processes that promote self-awareness, motivation, and problem-solving abilities. This approach is also more humanistic than traditional evaluative supervision models. However, its effectiveness is influenced by supervisor readiness, school culture, institutional support, and the sustainability of the mentoring process. This review concludes that coaching has significant potential as a supervisory strategy to meet modern educational demands for teacher professionalism. Practical implications include the need for coach training, continuous mentoring systems, and the integration of coaching into school supervision policies.. ABSTRAK Supervisi akademik berbasis coaching merupakan pendekatan pengembangan profesional yang menekankan kolaborasi, refleksi, dan pemberdayaan guru dalam meningkatkan kinerja pembelajaran. Artikel ini bertujuan menganalisis efektivitas coaching dalam supervisi akademik melalui kajian pustaka terhadap berbagai penelitian dan teori yang relevan. Dengan menggunakan metode narrative review, sumber-sumber dari lima tahun terakhir dianalisis untuk mengidentifikasi konsep dasar coaching, implementasinya dalam supervisi akademik, serta kontribusinya terhadap peningkatan kompetensi guru. Hasil kajian menunjukkan bahwa coaching mampu memperkuat kompetensi pedagogik, profesional, dan manajerial guru melalui proses dialogis yang mendorong kesadaran diri, motivasi, dan kemampuan pemecahan masalah. Pendekatan ini juga terbukti lebih humanis dibandingkan supervisi tradisional yang bersifat evaluatif. Namun, efektivitas coaching sangat dipengaruhi oleh kesiapan supervisor, budaya sekolah, dukungan institusi, serta keberlanjutan proses pendampingan. Kajian ini menegaskan bahwa coaching berpotensi menjadi strategi supervisi yang relevan untuk menghadapi tuntutan profesionalisme guru pada era pendidikan modern. Implikasi praktis meliputi perlunya pelatihan coach, sistem pendampingan berkelanjutan, dan integrasi coaching dalam kebijakan supervisi sekolah.